Visual Quality of Heritage Area of Pahlawan Street, Pasuruan City - Desy Suryya Fatmaningtyas; Jenny Ernawati (Jurnal Mahasiswa Jurusan Arsitektur, 2020)
Historic area has its own charm when it is well-designed. One of the historic area that recognized as heritage area by Pasuruan City Government is Jalan Pahlawan. For the sake of supporting the vitality of the heritage area, the city's government will revitalize Pahlawan Street by carrying heritage theme. So far, the revitalitation that have been done are pedestrian path improvement and colonial-themed street attributes addition. These effort have been realized  in half segment  of  Pahlawan Street. The visual quality study can be used as measurement tool in assessing the aesthetics of Pahlawan Street, with a mean score statistical method. The object of study is divided into two segments, segment I is a section of road that has not been revitalized and segment II, is a section of road that has been revitalized. This study uses a questionnaire survey method with 120 respondents in each segment with a nonprobability sampling technique.. Visual quality was tested using 6 aspects of visual quality, i.e: complexity, coherence, legibility, attractiveness, uniqueness and harmony in the form of questionnaires, and measured using a 7 point Likert scale. The study findings that the revitalized segment II as a whole is considered to have better visual quality and more representative of the historic area than segment I, also found that visually revitalized roads are more enjoyable than those that have not been revitalized.